Cardiac Late Sodium Channel Current Is a Molecular Target for the Sodium/Glucose Cotransporter 2 Inhibitor Empagliflozin. Issue 22 (2nd June 2021) - Philippaert, Koenraad; Kalyaanamoorthy, Subha; Fatehi, Mohammad; Long, Wentong; Soni, Shubham; Byrne, Nikole J.; Barr, Amy; Singh, Jyoti; Wong, Jordan; Palechuk, Taylor; Schneider, Chloe; Darwesh, Ahmed M.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: SGLT2 (sodium/glucose cotransporter 2) inhibitors exert robust cardioprotective effects against heart failure in patients with diabetes, and there is intense interest to identify the underlying molecular mechanisms that afford this protection. Because the induction of the late component of the cardiac sodium channel current (late- I Na ) is involved in the etiology of heart failure, we investigated whether these drugs inhibit late- I Na . Methods: Electrophysiological, in silico molecular docking, molecular, calcium imaging, and whole heart perfusion techniques were used to address this question. Results: The SGLT2 inhibitor empagliflozin reduced late- I Na in cardiomyocytes from mice with heart failure and in cardiac Nav1.5 sodium channels containing the long QT syndrome 3 mutations R1623Q or ΔKPQ. Empagliflozin, dapagliflozin, and canagliflozin are all potent and selective inhibitors of H2 O2 -induced late- I Na (half maximal inhibitory concentration = 0.79, 0.58, and 1.26 µM, respectively) with little effect on peak sodium current. In mouse cardiomyocytes, empagliflozin reduced the incidence of spontaneous calcium transients induced by the late- I Na activator veratridine in a similar manner to tetrodotoxin, ranolazine, and lidocaine. The putative binding sites for empagliflozin within Nav1.5 were investigated by simulations of empagliflozin docking to a three-dimensional homology model of human Nav1.5 and point mutagenic approaches. Our results indicate that empagliflozin binds to Nav1.5 in the same region as local anesthetics and ranolazine. In an acute model of myocardial injury, perfusion of isolated mouse hearts with empagliflozin or tetrodotoxin prevented activation of the cardiac NLRP3 (nuclear-binding domain-like receptor 3) inflammasome and improved functional recovery after ischemia. Conclusions: Our results provide evidence that late- I Na may be an important molecular target in the heart for the SGLT2 inhibitors, contributing to their unexpected cardioprotective effects.